2005
DOI: 10.1002/mrd.20359
|View full text |Cite
|
Sign up to set email alerts
|

Expression of morphogenic genes in mature ovarian and testicular tissues: Potential stem‐cell niche markers and patterning factors

Abstract: Morphogens are developmental regulators that modulate different tissue patterning, proliferation, differentiation, or remodeling processes in embryonic and adult tissues. Morphogens may also evoke specific regulatory programs in stem cells. Some of the morphogens involved in these processes have been characterized, while others remain unidentified. A microarray containing 3,557 salmonid cDNAs was used to compare the transcriptomes of rainbow trout precocious ovary at three different stages during second year (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 53 publications
0
22
0
1
Order By: Relevance
“…The significance of BMP signaling in the ovary is further highlighted by the increased ovulation rates in Booroola sheep with a point mutation in BMPR1B gene (Mulsant et al 2001, Souza et al 2001, Wilson et al 2001. Previous in situ hybridization and PCR-based studies have suggested that BMP4 is mainly synthesized in theca cells, corpus luteum, and other cells including stromal cells and acts in a paracrine manner to regulate granulosa cell function (Shimasaki et al 1999, Erickson & Shimasaki 2003, von Schalburg et al 2006, Abir et al 2008. Our previous report demonstrated that BMP4 promotes the transition of the primordial to primary follicle during follicular development (Tanwar et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of BMP signaling in the ovary is further highlighted by the increased ovulation rates in Booroola sheep with a point mutation in BMPR1B gene (Mulsant et al 2001, Souza et al 2001, Wilson et al 2001. Previous in situ hybridization and PCR-based studies have suggested that BMP4 is mainly synthesized in theca cells, corpus luteum, and other cells including stromal cells and acts in a paracrine manner to regulate granulosa cell function (Shimasaki et al 1999, Erickson & Shimasaki 2003, von Schalburg et al 2006, Abir et al 2008. Our previous report demonstrated that BMP4 promotes the transition of the primordial to primary follicle during follicular development (Tanwar et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, BMP4 mRNA is reported to be expressed in both granulosa and thecal cells of bovine, chicken, and mouse ovary (Onagbesan et al 2003, Fatehi et al 2005, von Schalburg et al 2006. Recently, BMP4 protein was detected in oocytes and granulosa cells of human ovary (Abir et al 2008), while growth differentiation factor 9 (GDF9) and BMP15 expression appear to be limited to the oocyte of the follicles throughout follicular development (Bodensteiner et al 1999, Erickson & Shimasaki 2003, Juengel et al 2004) except in primates, where GDF9 is also expressed in the cumulus and mural granulosa cells (Duffy 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Other authors have observed similar effects using colon cancer cells: OLFM-4 interfered with cytoskeleton filaments and caused cells to round up and detach. 9 OLFM-4 is particularly associated with tissues with high regenerative potential (ie, bone marrow, the gastrointestinal tract, prostate, murine ovaries, rat testis, 31 and endometrium). In addition, the fact that OLFM-4 affects processes such as cell adherence, cell-cell interaction, motility, and apoptosis, rather than proliferation, implies that this protein plays a determining role in differentiation of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a few reports on the expression of the Fzs in rodent ovary and testis (Ricken et al 2002, Hsieh et al 2005, von Schalburg et al 2006, there is no evidence showing the expression of Fzs in human germ cells. We have isolated human germ cells from adult testis as explained in the materials and methods section.…”
Section: Expression Of Wnts and Frizzled In Mouse Spermatogonia And Imentioning
confidence: 99%